2022
DOI: 10.1177/15562646221100430
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Critical Elements of Informed Consent in Genomic Research: A Case of a Paediatric HIV-TB Research Project in Uganda

Abstract: Several studies have reported inadequate comprehension of informed consent for genomic research. This study aimed to assess research participants’ understanding of critical elements of informed consent for genomic research. A cross-sectional survey involving 123 parents/caregivers of children participating in a paediatric genomic TB/HIV study was conducted. Only 47.2% of the participants had adequate understanding of consent information. The mean objective (actual) and subjective (perceived) understanding scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These approaches pose a challenge to informed consent for biobanking research in Africa because of the communitarian nature of society, customary beliefs, spirituality and relational autonomy (Akpa-Inyang & Chima, 2021). Recent studies from Uganda have reported inadequate understand of consent information in genetic and genomic research (Amayoa et al, 2022; Mwaka et al, 2021; Nabukenya et al, 2022; Rutakumwa et al, 2020); and this has been attributed to low genetic literacy, inaccuracy of translation of technical terminologies and concepts into local languages, reluctance of research participants to read informed consent documents in their entirety, key research team members not being well conversant with genetic/genomic concepts (Amayoa et al, 2022; Mwaka et al, 2021; Nabukenya et al, 2022), and ineffective community engagement approaches (Rutakumwa et al, 2020). Researchers therefore need to be flexible and reflexive enough in the way they think and approach the consenting process in genetic/genomic research (Barugahare, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches pose a challenge to informed consent for biobanking research in Africa because of the communitarian nature of society, customary beliefs, spirituality and relational autonomy (Akpa-Inyang & Chima, 2021). Recent studies from Uganda have reported inadequate understand of consent information in genetic and genomic research (Amayoa et al, 2022; Mwaka et al, 2021; Nabukenya et al, 2022; Rutakumwa et al, 2020); and this has been attributed to low genetic literacy, inaccuracy of translation of technical terminologies and concepts into local languages, reluctance of research participants to read informed consent documents in their entirety, key research team members not being well conversant with genetic/genomic concepts (Amayoa et al, 2022; Mwaka et al, 2021; Nabukenya et al, 2022), and ineffective community engagement approaches (Rutakumwa et al, 2020). Researchers therefore need to be flexible and reflexive enough in the way they think and approach the consenting process in genetic/genomic research (Barugahare, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Participants' concerns were an indicator that they did not adequately understand information about the procedure of disseminating the research findings before consenting to participation. Recent studies have reported a poor understanding of the informed consent process for pharmacogenomics and genomics research in Uganda (Amayoa et al, 2022;Nabukenya, 2019). An inadequate understanding of pharmacogenomics research procedures makes it difficult for participants to make informed decisions when choosing the different kinds of results they would prefer to receive.…”
Section: Discussionmentioning
confidence: 99%